ANÁLISE TEÓRICA E EXPERIMENTAL DAS PRESSÕES HORIZONTAIS ATUANTES NA FÔRMA DO SISTEMA DE TAIPA DE PILÃO - Rafael Monteiro Mendonca (2023)
Rammed earth or “taipa”, among many construction systems available in the building construction sector, has become a good option for professionals who want to build with energy efficiency and sustainability. Many publications (standards, manuals, books, papers, and thesis), establish minimum criteria for the construction, from soil preparation to formwork type options, however, the information on how these formworks are dimensioned is not clear, and the acting horizontal loads are hidden or unknown, especially those caused by the soil compaction effect. To fill this gap, a theoretical and experimental analysis became relevant, based on the analogy of the horizontal loads acting on the formwork, with theories for retaining walls, formwork for concrete walls, and loads acting on silos. A series of two test and one experiment were performed with undeformable formwork and sensors to obtain horizontal pressure data during the process of executing the rammed earth walls. It was possible to determine the magnitude of the horizontal loads, the significant influence of the tamper, the height of the already compacted mixture, from which the equipment no longer affects the formwork, only increasing vertical loads, possible movements/deformations of formwork, ratio of horizontal pressure to vertical pressure at any depth under the impact surface of the equipment. Tit is concluded that the proposed methodology for measuring the horizontal loads is promising for the equation of the problem, as well as outlining a scope for measurements with equipment of different weights and frequencies throught the application of Janssen’s silo theory, which allows for future similar tests for comparison and through this methodology and the hypotheses raised throughout the literature review are plausible.